Effect of glucose on biodegradation of hydrocarbons in crude-oil polluted soil undergoing bioremediation - Pedro, Peekate, Lekiah; Dein, Diepiriye, Anita; Chizoba, Amadi, Mishael (The Asia Journal of Applied Microbiology, 2023)
Bioremediation of crude oil polluted soil can be enhanced by addition of easily assimilated carbon sources such as glucose. The aim of this study was to determine the effect of increasing concentration of glucose on biodegradation of hydrocarbons in crude-oil polluted soil undergoing bioremediation. Some hydrocarbon utilizing bacteria and fungi were used as bioremediation agents in the study. Soil artificially polluted with crude-oil was divided into 5 setups: CT (control), S1, S2, S4, and S8. Suspension of the bioremediation agents and nutrients were added to the setups. About 5, 10, 20, and 40 g glucose were added to S1, S2, S4, and S8 respectively: equivalent to 1, 2, 4, and 8 % glucose concentration. Soil moisture in the setups was maintained at 10-20 % during the experimental period. Total hydrocarbon concentration (THC), and population of total heterotrophic bacteria (THB), hydrocarbon utilizing bacteria (HUB), total fungi (TF), & hydrocarbon utilizing fungi (HUF) were determined on day 1 and 21. Results obtained showed that increase in HUB occurred only in setup S1, and setup S1 had the highest extent of hydrocarbon degradation (18.93 %). Setup S8 had the lowest extent of hydrocarbon degradation (0.79 %). It is concluded that glucose concentration of 1 % and below will enhance biodegradation of hydrocarbons in crude-oil polluted soils, whereas high glucose concentration will retard hydrocarbon biodegradation. Also, the study indicates the possibility of fungi not partaking in hydrocarbon degradation when glucose is made available.